Fishers’ Local Ecological Knowledge to Support Mangrove Research in the Galapagos - Pontón-Cevallos, José; Ramírez-Valarezo, Nathaly; Pozo-Cajas, Mireya; Rodríguez-Jácome, Gabriela; Navarrete-Forero, Gabriela; Moity, Nicolas; Villa-Cox, Gonzalo; Ramírez-González, Jorge; Barragán-Paladines, María José; Bermúdez-Monsalve, Jorge R.; Goethals, Peter L. M. (Frontiers in Marine Science, 2022)
Mangroves provide multiple ecosystem services to coastal communities and their fisheries. In the Galapagos, mangroves have been primarily prized for their role as nursery grounds; though, the importance of cultural benefits, including the development of knowledge systems among fishers, needs to be further explored. Fishers’ local ecological knowledge (LEK) has been employed in the past to answer questions about the marine environment; not yet about mangroves. In such regard, this ethnoecological approach can contribute to unveil mangrove habitat-dependence relationships among fishery taxa across the life cycle, connectivity among habitats, and productivity spatial patterns across the archipelago. To access fishers’ LEK, we conducted 35 semi-structured interviews and 2 facilitated community workshops comprising 3 activities. A photo-elicitation method allowed us to extract values given to mangroves (i.e., ecosystem services), from which indirect use values were considered more relevant for fisheries. As such, the accumulation of LEK might have been crucial for the establishment of these values among fishers. By using a species-habitat association method, we revealed a high perceived connectivity between mangroves and other coastal and marine habitats in the Galapagos. Although this suggests an overall weak dependence to the ecosystem, fishers’ anecdotes allowed us to recognize novel species occurrences and exclusive habitat uses (e.g., spawning in Centropomus viridis). By applying Social Network Analysis to species-habitat association results, we learned that certain migratory commercial species (e.g., Lutjanus argentiventris, Seriola rivoliana) might constitute critical links in marine trophic webs and across seascapes. Finally, through scoring and participatory mapping methods, we revealed the prominence of western islands’ mangroves for fishery productivity, which were linked to biophysical attributes, like forest canopy and freshwater. Yet, other locations in central and southeastern islands might also be important, as they hold similar attributes. Interviews to other mangrove users (e.g., naturalist guides, park rangers, scientists; N = 33), and past scientific studies allowed us to triangulate LEK and to find complementarity among knowledge sources. Despite having an explorative focus, our work already showcases the potential of fishers’ LEK in improving mangrove research in the Galapagos, and the arising opportunities for ecosystem-based fisheries management and mangrove protection.